Fabrication and Characterization of Poly(vinyl alcohol)-chitosan-capped Silver Nanoparticle Hybrid Membranes for Pervaporation Dehydration of Ethanol - Manu L. Naik; Ashok M. Sajjan; T. M. Yunus Khan; Ashwini M; Sharanappa Achappa; Nagaraj R. Banapurmath; Narasimha H. Ayachit; Mostafa A. H. Abdelmohimen (Gels, 2022)
Chitosan-capped silver nanoparticle (CS-capped AgNPs)-incorporated Poly(vinyl alcohol) (PVA) hybrid membranes were prepared by a solution-casting technique for ethanol dehydration via pervaporation. The incorporation of CS-capped AgNPs into the PVA membrane and its influence on membrane properties and pervaporation-separation process of azeotropic water/ethanol mixture was studied. The addition of CS-capped AgNPs into the PVA membrane reduced the crystallinity, thereby increasing the hydrophilicity and swelling degree of the hybrid membrane, supported by contact angle (CA) analyzer and swelling degree experiments, respectively. Fourier transform infrared spectroscopy (FTIR) demonstrated the formation of polymeric matrix between PVA and CS and also the binding of AgNPs onto the functional group of CS and PVA, which was also reflected in the microstructure images demonstrated by scanning electron microscopy (SEM) and by 2θ angle of wide-angle X-ray diffraction (WAXD). The effect of CS-capped AgNPs on the thermal stability of the hybrid membrane was demonstrated by differential scanning calorimetry (DSC) and thermogravimetric analyzer (TGA). These characteristics of the hybrid membrane positively impact the efficiency of the dehydration of ethanol, as indicated by pervaporation experiments. The best performances in total flux (12.40 ± 0.20 × 10−2 kg/m2 h) and selectivity (3612.33 ± 6.03) at 30 °C were shown for CS-capped AgNPs PVA hybrid membrane containing 2 wt.% CS-capped AgNPs (M-4). This confirms that the developed hybrid membranes can be efficiently used to separate water from azeotropic aqueous ethanol.